Airway problems in children with lysosomal storage diseases - Arimoto, Yukiko; Yoshie, Urara; Kudo, Fumiyo; Nakano, Atsuko (Pediatric Otorhinolaryngology Japan, 2010)
Lysosomal storage diseases are caused by the lack of an enzyme in the cells that normally eliminates or breaks down other substances. Respiratory problems are frequently encountered by patients with lysosomal storage diseases. From 1990 to 2009, we treated 24 patients (17 male, 7 female): 8 with mucopolysaccharide storage disease, 6 with Gaucher disease, 5 with mucolipidosis II (I–cell disease), and 5 with other conditions. Adenotonsillectomies were performed for airway management in three cases of Hunter syndrome. One patient had surgery at the age of three years, three years before diagnosis of the disease. The other two patients had surgery after the diagnosis of the disease. The patients who underwent adenotonsillectomy suffered from upper airway obstructions after the adenotonsillectomies, and two of the three cases required tracheostomies. Seven of 24 (12.5%) required tracheostomies or laryngotracheal separation: 2 with Hunter syndrome, 2 with Gaucher disease, 2 with I–cell disease, and one with GM–2 gangliosidosis. The age at the time of surgery ranged from 9 months old to 19 years old (average 8.3 years). Of these cases, only one surgery took place before the diagnosis; the others took place an average of five years after diagnosis of the disease. Highly thickened skin, submucosal tissue, and tracheal wand, which are typical findings for mucopolysaccharide storage disease, were observed in one patient with Hunter syndrome at the time of operation. Complications after tracheostomy such as tracheal stenosis and granular formation in the trachea were observed in only two cases of Hunter syndrome. We concluded that the management and treatment for airway problems associated with lysosomal storage diseases should be considered case-by-case because of the wide variations in the clinical course.